PENGGUNAAN Trichoderma Koningii PADA PERKECAMBAHAN SIRSAK (Annona muricata linn) - Erida Derita Dalame; Bertje Richard Albert Sumayku; Jeany Polii - Mandang (Sam Ratulangi University, 2019)
This study aims to determine the dose of Trichoderma koningii which can induce soursop germination; know the best soaking time that can affect the induction of soursop germination; to know the interaction between soaking time and Trichoderma koningii dose on soursop germination. This research was conducted in April - June 2019 at the Green House of Plant Sciences, Faculty of Agriculture, Sam Ratulangi University, Manado. The material used in this study was soursop seed obtained from Lota Village, Pineleng Tomohon Subdistrict, Trichoderma koningii with 106 solids obtained from the North Sulawesi Province Plant Protection Center Collection, Aquadest, 70% Alcohol, 80% Acetone, sandalready sifter and sterilized. This research was arranged in factorial with a Completely Randomized Design (CRD) consisting of two factors, namely 5 treatments of Trichoderma koningii dose and 4 immersion treatments repeated three times (3x) so that a total of 60 treatment units. Each treatment unituses 10 seeds. The results of this study indicated that the dose of Trichoderma koninggi 200 g without soaking can increase the germination power by 86.67% and the vigor index by 32.96%; Immersion with Koninggi Trichoderma suspension has not been able to induce soursop seed germination rate; Theinteraction between Trichoderma koningii dose and soaking time did not affect the speed of soursop seed germination.*eprm*